2021
DOI: 10.5758/vsi.210016
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Peripheral Arterial Disease in Patients Undergoing Endovascular Revascularization for Chronic Limb Threatening Ischaemia: Insights from the Vascular Quality Initiative in Singapore

Abstract: This study aimed to examine the distribution of lower limb atherosclerotic lesions in a multi-ethnic Asian cohort with chronic limb threatening ischemia (CLTI) from Singapore. The Society for Vascular Surgery Vascular Quality Initiative registry database was used to identify 265 CLTI patients who underwent percutaneous angioplasty between June 2019 and December 2019, of whom 171 (64.5%) were male, and the mean age was 67.9±11.0 years. The majority were diabetic (84.5%) and 145 (54.7%) had chronic kidney diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Will this will have to be proven, present outcome data from PRESTIGE and XTOSI are encouraging especially for BTK vessels (Tang et al 2021a ; Choke et al 2021 ). In terms of treating long lesions, treatment with stents may not be suitable as long stents have issues such as occlusion, in particular in Asian vessels which are smaller than Caucasian vessels, and can be very difficult to reopen when occluded (Soon et al 2021 ). While there is a potential for distal embolisation and outflow obstruction resulting in impaired wound healing and increased LEA as with paclitaxel DCB, there have thus far been no slow flow phenomenon with sirolimus SCB (Tang et al 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Will this will have to be proven, present outcome data from PRESTIGE and XTOSI are encouraging especially for BTK vessels (Tang et al 2021a ; Choke et al 2021 ). In terms of treating long lesions, treatment with stents may not be suitable as long stents have issues such as occlusion, in particular in Asian vessels which are smaller than Caucasian vessels, and can be very difficult to reopen when occluded (Soon et al 2021 ). While there is a potential for distal embolisation and outflow obstruction resulting in impaired wound healing and increased LEA as with paclitaxel DCB, there have thus far been no slow flow phenomenon with sirolimus SCB (Tang et al 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher incidence of advanced CVD and CAD in CLTI patients as compared to patients with less severe PAD (Becker et al 2011 ). It has been found that the incidence of co-morbidities, proportion of severely diseased lesions and proportion of patients with tissue loss were higher in a Singaporean CLTI population than that of endovascular Western cohorts from the SVS VQI registry (Soon et al 2021 ). However, 6-month AFS in R6 patients following endovascular treatment in Western populations has been reported to be approximately 62–66%(Rocha-Singh et al 2012 ; Mustapha et al 2019 ), which is comparable to that of our study cohort (64.0%).…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher incidence of advanced CVD and CAD in CLTI patients as compared to patients with less severe PAD (Becker et al 2011). It has been found that the incidence of comorbidities, proportion of severely diseased lesions and proportion of patients with tissue loss were higher in a Singaporean CLTI population than that of endovascular Western cohorts from the SVS VQI registry (Soon et al 2021). However, 6-month AFS in R6 patients following endovascular treatment in Western populations has been According to the recent CIRSE standard of practice (2021) on below-the-knee (BTK) revascularisation, though POBA remains the first line treatment for long lesions, drug-eluting stents are regarded as "superior in terms of patency, target lesion revascularisation, Rutherford improvement and wound healing at 1-year follow-up, compared to bare metal stenting or plain balloon angioplasty" (Spiliopoulos et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous findings of more severe chronic comorbidities in the Asian population including diabetes and chronic kidney disease which contribute to the pattern of PAD. 14 The significance of the lower proportion of AC reporting being smokers compared to NAC is unknown and could possibly be due to the relative higher role of diabetic angiopathy compared to smoking in driving PAD in Asians or may also be partially explained by Asians being culturally less forthright in reporting their smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…13 This may be due to anatomical differences such as vessel size, as well as lifestyle factors such as diet. 10 A recently published study by Soon et al 14 found Asian CLTI patients to have multi-level long segment, highly calcified stenotic atherosclerotic disease, contrary to their Western counterparts. It is therefore not well established if the Asian cohort would benefit from revascularisation measures using DCB to the same extent as another ethnicity.…”
Section: Introductionmentioning
confidence: 99%